Development of Genetic Tools for the Chemolithoautotroph C. metallidurans CH34: Harnessing Synthetic Biology to Expand Knowledge of Extracellular Electron Transfer - Turco, Federico (2022)
Synthetic biology is based on engineering principles by assembling characterized genetic parts to redesign organisms with new abilities that can be used for the benefit of society. Among the list of microbial chassis under investigation for industrial purposes, the facultative chemolithoautotroph Cupriavidus metallidurans CH34 exhibits a series of qualities that makes it ideal for applications such as bioremediation, bioprocessing and generation of bioelectricity in Microbial Fuel Cells (MFCs). Nevertheless, the lack of genetic tools for strain development and for the study of fundamental physiological mechanisms, currently represents a bottleneck to boost commercial applications of C. metallidurans CH34. The main aim of this study was to develop a “toolkit starter-pack” to investigate physiological processes, such as extracellular electron transfer (EET) in C. metallidurans CH34 and to expand the repertoire of genetic tools available for its exploitation in the biotechnology industry. Firstly, Plasmid Addiction Systems (PASs) were developed and assessed in continuous growth conditions for stable plasmid maintenance and heterologous protein expression. Unfortunately, none of the PASs developed during this study achieved stable plasmid maintenance. Failure to develop a stable plasmid-based expression platform further highlighted the necessity of developing suitable tools and methodologies for chromosomal alterations, including chromosomal integrations of heterologous genes. Inducible and constitutive promoter libraries were built and characterized that served the dual purpose of i) providing a first comprehensive list of biological parts for regulation of protein expression and ii) to use these parts to optimize a CRISPR-Cas9 system that would allow efficient chromosomal alterations in C. metallidurans CH34. Subsequently, a single-plasmid CRISPR-Cas9 system that can be delivered by electroporation was successfully developed for fast, marker-less genome editing of C. metallidurans CH34. To my knowledge, this is the first marker-less genome editing tool developed for this organism that allows for precise gene deletions and integration of heterologous DNA. The genome editing system was validated and further exploited to study the mechanisms of EET in C. metallidurans CH34. Deletion targets were selected based on candidate genes encoding for type IV pili which are believed to be among the major actors for EET to solid surfaces in G. sulfureducens. As it was hypothesised that type IV pili might fulfil the same function in C. metallidurans CH34, single (ΔpilA, ΔpilE) and double deletions strains (ΔpilAE) were generated using the newly developed CRISPR-Cas9 system. The strain C. metallidurans CH34 ΔpilAE was further studied by means of Cyclic Voltammetry using disposable Screen-Printed Carbon Electrodes (SPCEs). No difference in current generation was found in deletion strains when compared to the wild type C. metallidurans CH34, suggesting that the type IV pilins were not involved in EET. Nevertheless, it was discovered that C. metallidurans CH34 was capable of generation of extracellular currents thanks to the use of both electroactive soluble mediators and molecules adsorbed on the electrode surface. Future work should include bolstering of the genetic toolbox by i) implementation of multiplex CRISPR-Cas9 systems for editing of multiple genes and expansion of the inducible and constitutive promoter libraries for precise regulation of gene expression ii) further elucidation of the EET mechanisms by means of omics disciplines and genetic studies of thick electrogenic biofilms of C. metallidurans CH34 in MFCs and iii) use of the tools developed to generate mutant strains for increased extracellular electron transfer. Altogether this work represents a significant advancement in terms of development of genetic tools and knowledge regarding EET mechanisms adopted by C. metallidurans CH34 that hopefully will bolster its exploitation in MFCs and other fields of biotechnology.